STUDY ANALYSIS OF SLOPE STABILITY ON BORED PILE REINFORCED DAM USING FINITE ELEMENT METHODE - SUNDARY (NIM : 25003011); Pembimbing : Ir. Suyud R. Karyasuparta, MSc, Ph.D, DEVI
This study conducted on slope stability of Waduk Keuliling Dam Kabupaten Aceh Besar, Nanggroe Aceh Darussalam, where modification was conducted on the downstream side by installing bored pile reinforcement. In the downstream, the slope was cut to create an open area which can be used for farming, recreation, sports area, etc. Slope cutting area has 30 meters long and 8 meters high. The analysis using the finite element method using Plaxis Geotechnic Program version 7. Reinforcement in the slope with bored pile, 1 meter in diameter and 18 meters long and 1,5 meters pile spacing. According to the result of the analysis, deformation are small and the mechanism of slope failure is rotation. The result of the calculation analysis shows that the safety factor is appropriate. Before the modification, the safety factor is higher than 1,5. Other wise the stability caused by the pseudo static earthquake in 144 years period, the safety factor shows higher than 1,2. On the slope stability analysis of the reinforced dam using bored pile shows the value of safety factor higher than 1,5. Under earthquake loading which was calculated by pseudo static method, the safety factor is higher than 1,2. Beside static analysis, seepage analysis under steady state condition and rapid drawdown were also calculated.